(untitled) (Praxis Educativa, 2026)
This paper proposes a critical reinterpretation of the origins of the Argentine public school system, focusing on a component that dominant historiography has rendered invisible: the influence of the “Protestant path” and the arrival of American teachers, summoned by Domingo F. Sarmiento in the 19th century, to reorganize the educational system. The central hypothesis is that the public school system was not born as an instrument of state discipline, but rather as an experiment in cooperation, popular sovereignty, democracy, secularism, republicanism, and feminist prefiguration. Heirs to the Protestant Reformation, the thought of Comenius, and the English Revolution, it transcended the liberal, Catholic, and cultural frameworks of a nascent state that, both immediately and subsequently, sought to discipline it. Methodologically, the paper combines global history, microhistory, and critical genealogy, concluding that the invisibility of the Protestant path constituted an active operation of symbolic closure, and its dismantling contributes to the historiographical redress of this initial meaning